Diffuse Hyperlymphocytosis cd8 Syndrome Initially Mistaken for Sarcoidosis - Fall B. C; Dieng M; Gaye A; Niang D; Sall A; Diaw B; Fall A; Salane A; Djiba B; Kane B. S; Sow M; Ndao A. C; et al. (International Journal of Applied Sciences: Current and Future Research Trends, 2022)
The syndrome of hyperlymphocytosis CD8 associated with HIV or "diffuse infiltrative lymphocytosis syndrome" (DILS) is a rarer pathology since the introduction of triple therapy. We report a new case of DILS taken initially for sarcoidosis. It was Miss A M 40 years old smoking weaned for 3 months; Followed in ophthalmology for panuvéite for 5 years under prednisone 1 mg / kg. This treatment was irregularly taken by the patient. At admission, she had a dry oculo-buccal syndrome, superficial polyadenopathy, sub-diaphragmatic superficial polyadenopathy, symmetrical bilateral parotidomalgia with pear-like appearance, asymmetrical bilateral crepitis in the pulmonary bases. Examination of the integuments found onyxis. The electrocardiogram was normal. Chest X-ray revealed an interstitial syndrome. Thoracic CT scan showed bilateral micronodular pulmonary images with lymph nodes in the upper non-compressive mediastinum and foci of lower lobar fibrosis. Bronchial biopsies showed non-specific inflammatory rearrangement. The alveolar broncho lavage found a lymphocytic alveolitis predominantly composed of CD8 T cells. The ophthalmological examination found sequelae lesions of panuvéite. Blood lymphocyte phenotyping found 161 CD4 / mm3 and 1855 CD8 / mm3 (CD4 / CD8 ratio = 0.086 [N> 0.68]). Investigations of a bacterial infection with benign or specific germs were negative. However, HIV1 serology was positive. The viral load was 110 copies / ml. The biopsy of a cervical adenopathy found a florid follicular lymphoid hyperplasia. The salivary gland biopsy showed lymphoplasmocytic infiltration of viral origin. A diagnosis of DILS was made and antiviral treatment was prescribed as well as corticosteroid therapy. CD8 hyperlymphocytosis decreased after 4 weeks of treatment. HIV-associated CD8 hyperlymphocytosis syndrome (DILS) is a rare entity, but should be systematically discussed in the presence of parotidomgalia and / or other organ damage associated with polyclonal CD8 lymphocytosis.